Regression of right ventricular systolic pressure after successful percutaneous mitral commissurotomy in patients with isolated severe mitral stenosis - Zeb, Shah (Pak J Med Sci, 2017)
OBJECTIVE: To know the regression of right ventricular pressure after successful percutaneous transluminalmitral commissurotomy (PTMC) in patients with severe isolated mitral stenosis. METHODS: This descriptive study was performed in inpatient and outpatient department of National Institute of Cardiovascular Disease from 1(st) February 2016 to 31(st) August 2016. Echocardiography of all patients with successful PTMC were recorded 24 hours and 06 months following PTMC to see for Regression of right ventricular pressure along with other baseline echocardiographic parameters. RESULTS: A total of 99 patients with severe isolated mitral stenosis who had undergone successful PTMC were studied. Females were 65(65.7%) and males 34(34.3%). Mean age was 27.44±6.26 years. TTE performed before and after PTMC showed significant difference in mean mitral valve area (0.89cm ±0.089cm2 vs. 1.68±0.128 cm2, p valve <0.001) and mean left atrial diameter (4.66± .82cm vs. 4.46± 0.65cm). Mean mitral valve gradient pre PTMC was significantly higher (16.38±2.51 mm of Hg) than that of post PTMC 24 hours (4.75±1.31 mm of Hg) and Post PTMC 06 months (5.22±1.21 mm of Hg), p valve <0.001. Mean right ventricular systolic pressure (RVSP) pre PTMC was significantly higher 62.3±10.91 mm of Hg than that of post PTMC 24 hour’s 57.51±9.67 mm of Hg and post PTMC 06 moths 46.49±7.8mm of Hg, p value 0.001. Mean LVEF 50.14± 5.82. CONCLUSION: There was a significant regression of right ventricular pressure following successful PTMC in mid-term (06 months) follow up of severe isolated mitral stenosis patients.